2013
DOI: 10.1902/jop.2012.110372
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Periodontal Disease in Rats Decreases Insulin Sensitivity and Insulin Signaling in Adult Offspring

Abstract: Background: Periodontal disease during pregnancy has been recognized as one of the causes of preterm and low‐birth‐weight (PLBW) babies. Several studies have demonstrated that PLBW babies are prone to developing insulin resistance as adults. Although there is controversy over the association between periodontal disease and PLBW, the phenomenon known as programming can translate any stimulus or aggression experienced during intrauterine growth into physiologic and metabolic alterations in adulthood. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 47 publications
5
26
0
2
Order By: Relevance
“…Similar results were observed by Shirakashi et al . (), who conducted a study in a maternal PD experimental model. It was found that adult offspring of these rats exhibit reduction in pp185 tyrosine phosphorylation after insulin stimulation in the GM and pWAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were observed by Shirakashi et al . (), who conducted a study in a maternal PD experimental model. It was found that adult offspring of these rats exhibit reduction in pp185 tyrosine phosphorylation after insulin stimulation in the GM and pWAT.…”
Section: Discussionmentioning
confidence: 99%
“…Shirakashi et al . () reported that adult offspring of rats with PD demonstrate IR and impairment in the initial steps of IS in the gastrocnemius muscle (GM) and the periepididymal white adipose tissue (pWAT). This suggested that localized oral inflammation during the gestational period can induce significant alterations in the IS pathway in adult offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Our studies have demonstrated that the adult offspring of rats with periodontal disease show an increase in plasma levels of TNF‐α . This cytokine can activate c‐Jun N‐terminal kinases (JNK), IκB kinase β/nuclear factor‐kappa B (IKKβ/NF‐κB) and extracellular signal‐regulated protein (ERK: ERK1 and ERK2) intracellular pathways that are involved in insulin resistance .…”
mentioning
confidence: 96%
“…Although the relationship between GDM and periodontitis is well established, further studies evaluating different populations are needed to improve the knowledge about this relationship (12). Shirakashi et al (13) have shown that maternal periodontal disease in rats may promote fetal programming. An increase in the degree of phosphorylation of IRS-1 serine in adipose tissue (that causes a decrease in insulin signal), as well as increased plasma concentrations of tumor necrosis factor alpha (TNF-α), interleukin 6 and resistin were observed in the adult offspring of rats with periodontal disease (13).…”
Section: Discussionmentioning
confidence: 99%
“…Shirakashi et al (13) have shown that maternal periodontal disease in rats may promote fetal programming. An increase in the degree of phosphorylation of IRS-1 serine in adipose tissue (that causes a decrease in insulin signal), as well as increased plasma concentrations of tumor necrosis factor alpha (TNF-α), interleukin 6 and resistin were observed in the adult offspring of rats with periodontal disease (13). Furthermore, periodontal pathogens can reach the amniotic cavity and cause adverse pregnancy outcomes, including preterm birth and/or low birth weight (14).…”
Section: Discussionmentioning
confidence: 99%